2018
DOI: 10.1515/joc-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

New Hybrid PAPR Reduction Techniques for OFDM-Based Visible Light Communication Systems

Abstract: Orthogonal frequency division multiplexing (OFDM) is used with visible light communication (VLC) systems to reduce the effects of inter-symbol interference (ISI) and to achieve communication with high speed of data transmission and huge bandwidth. However, OFDM-based VLC systems suffer from high peak-to-average power ratios (PAPRs). This paper proposes a new hybrid PAPR reduction technique based on signal transformation combined with clipping. The Hadamard transform is used in the proposed technique due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The PAPR of the three-layer superimposed signals becomes [24]       It was found that oversampling=4 should be used as the best tradeoff between efficiency and computational complexity, correct with the theoretical analysis [9].…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…The PAPR of the three-layer superimposed signals becomes [24]       It was found that oversampling=4 should be used as the best tradeoff between efficiency and computational complexity, correct with the theoretical analysis [9].…”
mentioning
confidence: 72%
“…In a traditional VLC scheme based on OFDM or FBMC, bias values equal to the absolute minimum value are applied. Several state-of-the-art methods are used for comparison: Hadamard transform with clipping ratio=1.8 [20], Discrete cosine transform, and clipping ratio=1.8 [24] in term of PAPR and BER performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations